Answer:
Explanation:
6)Let the number be x
Product of a number and -4 = x * -4 = -4x
Product of a number and -4 increase by 3 : -4x + 3
-4x +3 = 9
Subtract 3 from both sides
-4x + 3 - 3 = 9 - 3
-4x = 6
Divide both sides by (-4)
-4x/-4 = 6/-4
x = -3/2
x = -1 1/2
7)Let the number be x
![(x)/(6)-9=11\\\\](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ey1gp6m25gm4p8nh56k1h8hb097nej3de8.png)
Add 9 to both sides
![(x)/(6)-9+9=11+9\\\\(x)/(6)=20\\](https://img.qammunity.org/2021/formulas/mathematics/middle-school/1a2a81jksfac8k8rvbo17b011g1085tli5.png)
Multiply both sides with 6
![(x)/(6)*6=20*6\\\\](https://img.qammunity.org/2021/formulas/mathematics/middle-school/alagrjf52077c7jhwdxm8yz7h8epl1x2kc.png)
x = 120